Collapse: How Societies Choose to Fail or Succeed (Civilizations Rise and Fall #2) - Jared Diamond (England Penguin Books, 2011)
Brilliant, illuminating, and immensely absorbing, Collapse is destined to take its place as one of the essential books of our time, raising the urgent question: How can our world best avoid committing ecological suicide? In his million-copy bestseller Guns, Germs, and Steel, Jared Diamond examined how and why Western civilizations developed the technologies and immunities that allowed them to dominate much of the world. Now in this brilliant companion volume, Diamond probes the other side of the equation: What caused some of the great civilizations of the past to collapse into ruin, and what can we learn from their fates? As in Guns, Germs, and Steel, Diamond weaves an all-encompassing global thesis through a series of fascinating historical-cultural narratives. Moving from the Polynesian cultures on Easter Island to the flourishing American civilizations of the Anasazi and the Maya and finally to the doomed Viking colony on Greenland, Diamond traces the fundamental pattern of catastrophe. Environmental damage, climate change, rapid population growth, and unwise political choices were all factors in the demise of these societies, but other societies found solutions and persisted. Similar problems face us today and have already brought disaster to Rwanda and Haiti, even as China and Australia are trying to cope in innovative ways. Despite our own society's apparently inexhaustible wealth and unrivaled political power, ominous warning signs have begun to emerge even in ecologically robust areas like Montana. Brilliant, illuminating, and immensely absorbing, Collapse is destined to take its place as one of the essential books of our time, raising the urgent question: How can our world best avoid committing ecological suicide?
Keywords: Civilization; Anthropology; History; Nonfiction; Sociology; Science; Politics; Environment; (BIN1064) Global Citizenship; Global Citizenship (BIN1064-N)